The-state-Art of steelmaking technology based on hydrogen metallurgy - Jiang , ZhouHua; Yang , Ce; Zhu , HongChun; Lu , HongBin (Theory and Practice of Metallurgy, 2025)
This paper puts forward the viewpoint that “hydrogen steelmaking” replaces “oxygen steelmaking”, and summarizes and evaluates the research status of “hydrogen steelmaking”. Hydrogen metallurgy steelmaking has unique advantages in energy saving, consumption reduction and product quality improvement. On the one hand, hydrogen has a highly efficient melting effect, which can effectively reduce the energy consumption of steelmaking. “Hydrogen” in plasma state has the characteristics of high temperature and high thermal conductivity, which can be used as a highly efficient heat source to realize the melting of charge and heating of steel, and has been applied in steelmaking processes such as EAF, converter and tundish. Blowing gaseous “Hydrogen” can accelerate the homogenization in the composition and temperature, and the movement of hydrogen bubbles can be adhered to the non-metallic inclusions which can be accelerated to float out. At the same time, hydrogen reacts with oxygen in the liquid steel to release a large amount of heat, which improves the thermodynamic and kinetic conditions of the melt pool reaction. In addition, “Hydrogen” can inhibit oxidation and reduce the loss of Cr, Mn and other alloying elements by creating a reducing atmosphere. On the other hand, “Hydrogen” has a non-polluting refining effect that significantly improves the cleanliness of the steel. Based on the high activity and high reducibility of “Hydrogen”, “Hydrogen” can effectively remove impurity elements such as O, C, N, S and P in steel, especially “Hydrogen” in plasma state, which can directly react with the impurity elements to generate H2O, CH4, NH3, H2S and PH3 and other gaseous products that are easy to be volatilized and removed, so as to avoid the formation of non-metallic inclusions, and to realize the highly efficient and high-cleanliness steelmaking with “zero inclusions”. Therefore, the development of a new generation of green, near-zero carbon, “zero inclusion” and pollution-free steelmaking process using “hydrogen” instead of “carbon” will accelerate the green, high-quality, and sustainable development of the steel industry.